Kalcinacije in mikrokalcinacije - Rener, Miljeva (Radiology and oncology (Ljubljana), 1998)
Microcalcinations are typical for a good third of the breast carcinomas and, due to them, carcinomas may be detected in a very early, pre-invasive stage, when the prognosis is still promising. The most essential image diagnostic method is mammography; at our Institute, we sometimes combine it with x-ray guided fine-needle aspiration biopsy or US. Looking for the right decision between false positive and false negative examination results, is like navigating between Scylla and Charybda; therefore, a radiologist, has to be loaded with thorough knowledge and rich experience.
Keywords: Breast neoplasms; Calcinosis; Diagnosis; diagnostika; dojke; Mammography; mamografija; novotvorbe; Pathology; rak (medicina)